Friedensdemonstration: eine Frau trägt einen Regenschirm mit der Aufschrift "Nie wieder Krieg"
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politisches Leben (speziell);Demonstration